Disclosures and perceptions of practitioners on items of financial and social reporting index developed for Malaysian Islamic Banks - Marsidi, Asri; Annuar, Hairul Azlan; Abdul Rahman, Abdul Rahim (Faculty of Economics and Business, Universiti Malaysia Sarawak, 2017)
The study examines the views of accountants concerning the importance of items in the developed index for Islamic Financial and Social Reporting (IFSR) as well as measures and discusses the level of weighted IFSR for Islamic banks based on the IFSR index developed for Malaysian Islamic banks. The research uses the questionnaires and the annual reports to collect the relevant data with respect to the views of accountants and IFSR score of Islamic banks respectively. The findings suggest that the financial part, and the auditing and governance part in the index of IFSR are important and close to important, respectively, while the social part is viewed as fairly important. Moreover, the other finding reflects that the weighted IFSR for Islamic banks in Malaysia is considered as fair. The findings with respect to the level of weighted IFSR disclosure may not be generalised to the years prior and after the examination period. The research provides empirical insights on the importance of items in the IFSR index and the weighted level of IFSR practices among Malaysian Islamic banks. The paper highlights the importance of items in the IFSR index as well as IFSR disclosure in enhancing the accountability and sustainability of Islamic banks.